2015
DOI: 10.1245/s10434-015-4926-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surgery Type and Chemotherapy on Early-Stage Breast Cancer Patients’ Quality of Life Over 2-Year Follow-up

Abstract: Purpose We examined the effects of surgery type and adjuvant chemotherapy on change in early-stage breast cancer patients' quality of life (QOL) over time. Methods A cohort of 549 patients (33.5% ductal carcinoma in situ, 66.5% stages I/IIA) were interviewed a mean 6.1 weeks (Time1), and 6.2 (Time2), 12.3 (Time3), and 24.4 (Time4) months following definitive breast-conserving surgery (BCS) or mastectomy. QOL was measured using the total Functional Assessment of Cancer Therapy-Breast (FACT-B). Adjusting for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 65 publications
2
22
1
4
Order By: Relevance
“…However, since breast cancer patients treated with RT report persistent fatigue years after completing treatment [49,70] and cancer-related fatigue is associated with worse QOL in long-term breast cancer survivors [70], future research is warranted to determine if less severe RT-related side effects in the short-term are associated with improved long-term QOL in breast cancer survivors. Jeffe et al reported that the adverse effect of chemotherapy on total FACT-B scores was more prominent in early-stage breast cancer patients who received BCS than mastectomy, suggesting that this finding was potentially due to the cumulative effects of RT following BCS [71]. Findings reported here suggest further that the negative cumulative effect of RT on change in both Vitality and the FACT-B total scores over two-year follow-up occurs regardless of type of RT received after definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, since breast cancer patients treated with RT report persistent fatigue years after completing treatment [49,70] and cancer-related fatigue is associated with worse QOL in long-term breast cancer survivors [70], future research is warranted to determine if less severe RT-related side effects in the short-term are associated with improved long-term QOL in breast cancer survivors. Jeffe et al reported that the adverse effect of chemotherapy on total FACT-B scores was more prominent in early-stage breast cancer patients who received BCS than mastectomy, suggesting that this finding was potentially due to the cumulative effects of RT following BCS [71]. Findings reported here suggest further that the negative cumulative effect of RT on change in both Vitality and the FACT-B total scores over two-year follow-up occurs regardless of type of RT received after definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that youth increases the likelihood of RTW in the year after diagnosis (11,12), and that chemotherapy is the major medical barrier to RTW (10,12,13). Indeed, the deleterious impact of chemotherapy on quality of life 1 (QOL) is well-known (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QoL) is an important consideration in oncology, particularly for patients with BC, and can also be affected by treatments . Maintenance of and improvements in QoL for patients with cancer during and after treatment are major concerns in oncology, because treatments are often intensive and traumatic .…”
Section: Introductionmentioning
confidence: 99%
“…1 Quality of life (QoL) is an important consideration in oncology, particularly for patients with BC, and can also be affected by treatments. 4,5 Maintenance of and improvements in QoL for patients with cancer during and after treatment are major concerns in oncology, because treatments are often intensive and traumatic. 6 For instance, the type of surgery or adjuvant therapy can induce several side effects and symptoms, such as anxiety or sleep disturbance, that can negatively affect personality and QoL.…”
Section: Introductionmentioning
confidence: 99%